Expression Of Gender Roles And The Concepts Of Loyalty And Betrayal In Literary Images - Jabborova E.R. (International Journal Of Literature And Languages, 2025)
This article analyzes the artistic interpretation of gender roles and the motifs of loyalty and betrayal in literary images. It examines the emergence of the gender approach as a methodological criterion in 20th–21st century literature, the representation of male and female characters within socio-cultural contexts, and the linguistic, psychological, and aesthetic dimensions in which the concepts of loyalty and betrayal are interpreted. Using examples from Uzbek and world literature, the article demonstrates how loyalty is associated with devotion, duty, and spirituality, while betrayal is connected with freedom, personal interest, or inner crisis. It is emphasized that contemporary literature revisits gender stereotypes and, through literary images, reflects society’s changing values from a new aesthetic perspective.